2016
DOI: 10.1039/c5ib00281h
|View full text |Cite
|
Sign up to set email alerts
|

Conserved roles for cytoskeletal components in determining laterality

Abstract: SUMMARY Consistently-biased left-right (LR) patterning is required for the proper placement of organs including the heart and viscera. The LR axis is especially fascinating as an example of multi-scale pattern formation, since here chiral events at the subcellular level are integrated and amplified into asymmetric transcriptional cascades and ultimately into the anatomical patterning of the entire body. In contrast to the other two body axes, there is considerable controversy about the earliest mechanisms of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 109 publications
2
36
0
Order By: Relevance
“…For example, in studying proteins with roles in early embryonic asymmetries [188], and in particular cytoskeletal proteins with a conserved role in determining embryonic laterality [86,87], the number of embryos with reversed organs is actually smaller than the number with incorrect Nodal expression, particularly for intracellular motor protein family myosins (table 1). This suggests that the pathway from Nodal to organ situs is not as linear as had been assumed: having incorrect Nodal expression does not actually mean that an embryo's organs will be reversed, despite Nodal's established role as a determinant or 'master regulator' of LR situs.…”
Section: Results: Endogenous Repairing Of Induced Left -Right Defectsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, in studying proteins with roles in early embryonic asymmetries [188], and in particular cytoskeletal proteins with a conserved role in determining embryonic laterality [86,87], the number of embryos with reversed organs is actually smaller than the number with incorrect Nodal expression, particularly for intracellular motor protein family myosins (table 1). This suggests that the pathway from Nodal to organ situs is not as linear as had been assumed: having incorrect Nodal expression does not actually mean that an embryo's organs will be reversed, despite Nodal's established role as a determinant or 'master regulator' of LR situs.…”
Section: Results: Endogenous Repairing Of Induced Left -Right Defectsmentioning
confidence: 99%
“…This model has been linked to data on birth defects and epithelial morphogenesis in humans and mice [104]. As in Xenopus, the mouse model has also revealed that a-tubulin organization is critical for asymmetry, via studies of the protein Mahogunin [84,86,87,105,106].…”
Section: Physics Upstream and Downstream Of Transcriptional Networkmentioning
confidence: 99%
See 3 more Smart Citations